Analisis Pemanfaatan Limbah Terak Nikel (Slag) sebagai Bahan Baku Pembuatan Shotcrete dan Penanganan Limbah Lumpur Nikel (Slurry) untuk Mengurangi Dampak Pencemaran Lingkungan - Ardhymanto Am Tanjung; Rahul Gonzales; Azizah Seprianti; Rahma Izati (Jurnal Migasian, 2022)
There are 21 million tons of nickel deposits in Indonesia, which produced 800,000 tons in 2019. Theamount of nickel waste has increased because of the high nickel production rate. Both liquid and solid by-products of nickel processing, slurry, and slag, are created. The amount of tailings slurry produced annually in Indonesia is up to 25.6 million tons, compared to 13 million tons of nickel slag. Nickel slag can be recycled since it contains valuable metals, including nickel, cobalt, and copper. The chemical composition of 70% nickel slag is 41.47% Silica, 30.44% Ferric Oxide, and 2.58% Alumina. An inventive solution to replace components of shotcrete with nickel slag was discovered through literature research. On the other hand, some businesses intend to use a technology to tackle the slurry nickel, known as "Deep Sea Tailing Placement (DSTP), to dispose of nickel sludge waste on the ocean floor. However, the government has not approved this DSTP method because it might harm marine habitats. This research discussed the benefits and drawbacks of the Deep-Sea Tailings Placement (DSTP) approach and the onshore tailings disposal method. This document can serve as a starting point for the usage of shotcrete in the mining sector and is hoped to be a resource for mining businesses looking to dispose of tailings on land or at sea.